Study of Rheological Behaviour and Thermal Degradation in Vegetable Oils on Heating - Rubalya Valantina, S.; Neelamegam, P. (Asian Journal of Chemistry, 2012)
Study of viscosity of vegetable oils is an important engineering parameter for designing processing equipment. The rheological and thermal degradation in unheated and heated rice bran oil, mustard oil, sesame oil and groundnut oil is studied as a function of temperature (30 to 90 ºC) using temperature controlled redwood viscometer. The viscosity decreased with increasing temperature at different rates depending on the saturated and unsaturated fatty acid composition of the oils. Some experimental relations that describe the temperature dependence of viscosity are fitted to experimental data and correlation constants are studied. The amount of polyunsaturated chains is better correlated (R2 = 0.896) with viscosity than monounsaturated chains. The content of unsaturated fatty acids has good correlation (R2 = 0.867) with viscosity than saturated fatty acids (R2 = 0.747) for unheated oils and heated oils. It is observed that the viscosity of heated (to smoke point 210 - 250 ºC) oil sample is greater than unheated oil due to increase in the content of saturated composite in the oil on heating.